Employer Image and Employer Brand: Interaction of Both Terms - Vecuma-Veco, Annija (Vilnius University Proceedings, 2024)
Currently, when the demand for employees is higher than supply, there is a question of possible solutions. One of the opportunities for companies is to ensure that they will be chosen when their potential employees consider making career changes. This is where the terms “employer image” and “employer brand” come into the picture – terms often used interchangeably in the scientific and professional fields. The aim of the article is to eliminate the confusion in the use of employer brand and employer image as terms and to show their theoretical position among other interconnected terms. It is presented through definitions and a model proposed by the author. In addition, the author points to the consideration of ethics when applying the employer brand.